Neurocognitive predictors of metacognition in individuals at clinical high risk for psychosis. Issue 2 (15th March 2020) - Shakeel, M.K.; Lu, L.; Woods, S.W.; Perkins, D.O.; Addington, J.
Abstract: Background: Metacognition refers to the ability to evaluate and control our cognitive processes. While studies have investigated metacognition in schizophrenia and clinical high risk for psychosis (CHR), less is known about the potential mechanisms which result in metacognitive deficits. Aims: We aimed to investigate whether neurocognitive functions including attention, working memory, verbal learning and executive functions predicted the tendency to focus on one's thoughts (cognitive self-consciousness) and beliefs in the efficacy of one's cognitive skills (cognitive confidence). Method: Participants (130 CHR individuals) were recruited as part of the multi-site PREDICT study. They were assessed using the Metacognitions Questionnaire (MCQ) as well as measures of executive function (WCST), attention (N-Back), working memory (LNS) and verbal learning (AVLT). Results: Cognitive competence was negatively correlated with N-Back while cognitive self-consciousness was positively correlated with N-Back and LNS. Linear regression analysis with N-Back, AVLT, LNS and WCST as predictors showed that neurocognition significantly predicted cognitive self-consciousness, with N-Back, LNS and WCST as significant predictors. The model accounted for 14% of the variance in cognitive self-consciousness. However, neurocognition did not result in a significant predictive model of cognitive competence. Conclusions: Neurocognition was associated with an increased focus on one's thoughts, but it was not associated with higher confidence in one's cognitive skills. Neurocognition accounted for less than one-sixth of the variance in metacognition, suggesting that interventions that target neurocognition are unlikely to improve metacognitive abilities.